Detection of Financial Distress Mediated by Fraudulent Financial Statements with the F-Score and Z-Score Approach in the Pandemic Era Listed on the Indonesia Stock Exchange - Wildatul Muawanah; Rida Perwita Sari (PT FORMOSA CENDEKIA GLOBAL, 2023)
The purpose of this study is to detect bankruptcy caused by financial statement fraud in companies listed on the Indonesian Stock Exchange (IDX) with a detection tool, namely fraud pentagon theory which consists of stimulus, ability, opportunity, rationalization and ego with the F-Score and Z methods -Scores. This study uses a descriptive quantitative approach using Smart PLS 4.0. The population of this research is the property & real estate, transportation & logistics sub-sector companies listed on the Indonesia Stock Exchange for the 2020-2022 period with a sample of 32 companies. The results of this study indicate that there is a strong indication of the effect of stimulus and ability on financial distress. Opportunity, rationalization, and ego have no effect on financial distress. Fraudulent financial statements cannot mediate the influence of stimulus, ability, opportunity, rationalization and ego on financial distress.